2018
DOI: 10.1016/j.jsxm.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Vulvodynia Treatments and 6-Month Outcomes for Women Enrolled in the National Vulvodynia Registry—An Exploratory Prospective Study

Abstract: Strengths include a prospective and long-term study design that evaluated women in clinical settings. Limitations include a high rate of loss to follow-up for certain measures and inability to evaluate efficacy of individual treatments. In a setting where women were receiving highly specialized care, we found wide variation in the type and number of treatments used to treat vulvodynia. Despite this heterogeneity in treatment selection, women reported significant improvements in all study measures except sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Significant improvement or complete remission may occur, spontaneously or following treatment. [145][146][147] Signs Inspection of the vulva reveals no relevant physical findings which means that the vulva has a normal appearance or that, if a lesion is found, this lesion cannot explain the discomfort (example: a wart cannot explain diffuse burning; LS usually explains itch and not pain).…”
Section: S -Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Significant improvement or complete remission may occur, spontaneously or following treatment. [145][146][147] Signs Inspection of the vulva reveals no relevant physical findings which means that the vulva has a normal appearance or that, if a lesion is found, this lesion cannot explain the discomfort (example: a wart cannot explain diffuse burning; LS usually explains itch and not pain).…”
Section: S -Severitymentioning
confidence: 99%
“…Vulvodynia is a chronic pain condition having usually lasted months or years before the diagnosis is made. Significant improvement or complete remission may occur, spontaneously or following treatment 145–147 …”
Section: Clinical Featuresmentioning
confidence: 99%
“…In the study by Trutnovsky et al [ 53 ], history of vulvar pain ranged from 3 months to 20 years in the surveyed patients. Lamvu et al [ 54 ] reported that the women in their study contacted a specialist around 2 years after the onset of vulvodynia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Each qualitative pain descriptor is then rated on the 4-point pain intensity scale and added for the final score. SF-MPQ subscales have been successfully used to measure treatment responses in vulvodynia [ 32 ].…”
Section: Patients/materials and Methodsmentioning
confidence: 99%